Slowly Learning the Hard Way: U.S. America’s War on Drugs And Implications for Mexico - Glen Olives Thompson (Norteamérica)
U.S. America’s aggressive drug enforcement policy, costing over US$1 trillion and putting millions of people in prison for casual drug use, is an abject failure. By regulating drug use rather than criminalizing it, per capita recreational drug use in the United States would be the same or even lower than it currently is, safer for consumers, and far less costly to society in terms of socioeconomic harm. This failed policy has not only affected U.S. society in such a harmful way that it almost cannot be overstated, but it has also resulted in quite needless drug cartel violence in Mexico and other countries. Included here is a pragmatic suggestion for reform of U.S. drug policy